1988
DOI: 10.1126/science.3201231
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Mutation Associated with Leber's Hereditary Optic Neuropathy

Abstract: Leber's hereditary optic neuropathy is a maternally inherited disease resulting in optic nerve degeneration and cardiac dysrhythmia. A mitochondrial DNA replacement mutation was identified that correlated with this disease in multiple families. This mutation converted a highly conserved arginine to a histidine at codon 340 in the NADH dehydrogenase subunit 4 gene and eliminated an Sfa NI site, thus providing a simple diagnostic test. This finding demonstrated that a nucleotide change in a mitochondrial DNA ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
1,020
1
18

Year Published

1993
1993
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,148 publications
(1,046 citation statements)
references
References 31 publications
7
1,020
1
18
Order By: Relevance
“…The m.11778G4A mutation in MT-ND4 gene is the most common mutation in patients with Leber hereditary optic neuropathy. 43,44 Although impaired hearing does not generally accompany Leber hereditary optic neuropathy, 45,46 appreciable progressive auditory neuropathy in two patients with Leber hereditary optic neuropathy has been reported. 47 However, the proband (TMD 455) in this study had never complained of any visual problems as is normally observed in cases with Leber hereditary optic neuropathy, nor did any of her family members.…”
Section: Discussionmentioning
confidence: 99%
“…The m.11778G4A mutation in MT-ND4 gene is the most common mutation in patients with Leber hereditary optic neuropathy. 43,44 Although impaired hearing does not generally accompany Leber hereditary optic neuropathy, 45,46 appreciable progressive auditory neuropathy in two patients with Leber hereditary optic neuropathy has been reported. 47 However, the proband (TMD 455) in this study had never complained of any visual problems as is normally observed in cases with Leber hereditary optic neuropathy, nor did any of her family members.…”
Section: Discussionmentioning
confidence: 99%
“…Treating all those carrying the most common mutation might perhaps be one option, but as only 50% of male and 10% of female patients carrying the G11778A LHON mutation actually develop visual loss, this would be likely to involve significant risk to healthy eyes. 30 It is also possible that injecting the virus after the visual loss has developed might be too late, especially as there is a lag of several weeks before optimal AAV-mediated transgene expression. Given the high risk of bilateral visual loss in LHON, perhaps the most realistic first approach in humans might be to treat the fellow eye after the visual loss has occured in the first eye.…”
Section: Optic Nerve Diseases Potentially Treatable By Gene Therapymentioning
confidence: 99%
“…After this discovery it soon became evident that defects in energy production were also present in patients with certain encephalomyopathic syndromes. However, it was not until 1988, when the first disease-causing mtDNA mutations were reported, that a molecular genetic basis for these disorders was discovered [7,8]. The molecular genetic aspects of mitochondrial diseases have recently been reviewed in depth [9] and the human mitochondrial genome database (MITOMAP; http://www.gen.emory.edu./mitomap.html) describes known mutations.…”
Section: Classical Mitochondrial Diseasesmentioning
confidence: 99%
“…The complete sequences of human [5] and mouse [6] mtDNA were reported in 1981, a pioneering achievement in the area of genome sequencing. However, the genetic basis of mitochondrial disorders remained obscure until 1988 when the first disease-causing mutations of mtDNA were found [7,8]. This discovery led to a rapid surge in the research into mitochondrial disorders, and there are now more than 50 different mtDNA mutations linked to human disease [9].…”
Section: Introductionmentioning
confidence: 99%